Green pull motives and overall tourist satisfaction: a macro- and micro-levels analysis. Issue 4 (5th March 2021) - Pekovic, Sanja
Abstract : Purpose: The environmental sensitivity of consumers has played an important role in shaping the tourism industry. Although the green trend is an ongoing concern within the tourism industry, empirical research examining the link between green motivation and tourist satisfaction has been lacking in the tourism literature. The study bridges this research gap by examining the relationship between green pull motives and overall tourist satisfaction using empirical data from 28 Member States of the European Union and Turkey, North Macedonia, Iceland, Montenegro and Moldova. Moreover, the framework incorporates both macro- and micro-level analyses, thus offering an unbiased approach compared to analyses based on a single-level perspective. The purpose of this paper is also to compare the relationship between green pull motives and tourist satisfaction across different generational cohorts, thus offering new insights into tourist satisfaction across life-courses. Design/methodology/approach: Through an examination of 7, 450 tourists from 28 Member States of the European Union and Turkey, North Macedonia, Iceland, Montenegro and Moldova derived from the Flash Eurobarometer survey called "Preferences of Europeans towards tourism, " the authors used a Tobit model to test the proposed framework. Findings: The obtained findings demonstrate that the green pull motives at the macro level are negatively associated with overall tourist satisfaction. In contrast, the green pull motives at the micro level are positively related to overall tourist satisfaction. In addition, the results show that the relationship between green pull motives and overall tourist satisfaction diverges between different generational cohorts. Practical implications: These results have wide implications for tourism marketers across different European countries, suggesting that adequately managing attributes associated with green motives at both the macro and micro levels, as well as across life-course, considerably contributes to overall tourist satisfaction. Originality/value: The novel findings increase understanding of the impact of green trends within the tourism sector by providing unbiased analysis of the relationship between green pull motives and overall tourist satisfaction that involves both a multilevel approach and generational cohort comparisons across life-course.